Platelet counts as a biomarker in ANCA-associated vasculitis. (July 2015) - Willeke, P; Kümpers, P; Schlüter, B; Limani, A; Becker, H; Schotte, H
<x xml:space="preserve">Abstract</x> Objectives: To determine whether platelet (PLT) counts might serve as a biomarker to distinguish between active anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and remission and also between active disease and systemic infection. Method: PLTs were analysed before treatment in patients with AAV in the active state and in remission. PLTs were also analysed in AAV patients with acute infections. The results were correlated with clinical manifestations, the Birmingham Vasculitis Activity Score version 3 [BVAS(v.3)], and other laboratory findings [i.e. C-reactive protein (CRP), leucocytes, differential count, procalcitonin (PCT)]. Diagnostic accuracy was calculated with a receiver operating characteristic (ROC) curve. Results: PLT counts were significantly increased in 98 patients with AAV during the active disease state [median: 405 PLTs/nL; interquartile range (IQR) 288–504] compared to patients in remission (246 PLT/nL; IQR 214–289) (p < 0.001). We found a correlation of PLT counts in active disease with the BVAS(v.3) (r = 0.582, p < 0.001). In AAV patients with systemic infections (n = 37), PLT counts exhibited significantly lower values (226 PLT/nL; IQR 163–273) compared to patients with active disease (p < 0.001). In the ROC curve analysis, the area under the curve (AUC) of PLTs was significantly larger when distinguishing active disease from systemic infection (AUC 0.868) compared to leucocytes (AUC 0.590), CRP (AUC 0.522), or procalcitonin (AUC 0.515) (p < 0.001). Conclusions: PLT counts were found to correlate with disease activity in AAV and thus may be used to represent immunological activity. In addition, PLT counts serve as a marker that can distinguish acute infection from active disease.